Analisis Kegiatan Komunikasi Pemasaran IndiHome Oleh PT. Telkom Indonesia Regional III Untuk Menjadi Brand Top Of Mind - Wibisono, Novel Gumilang; Dianita, Indria Angga; Arifputri, Aiza Nabila (eProceedings of Management, 2023)
This research aims to find out IndiHome marketing communication by PT.Telkom Indonesia (Regional III) held to realize becoming a Top of Mind Brand, by applying an integrated marketing communication theory from William G.Nickels (2007) which consists of Advertising, Sales Promotion, Public Relations and Publicity, Personal Selling and also Direct Marketing, the second based on Durianto's theory Through a qualitative approach and descriptive research types, the stages carried out in this research are advertising, sales promotion & event, personal selling, Direct marketing and top of mind. The results of this research are: 1) Advertising, which is an advertising activity carried out by PT.Telkom Indonesia (Regional III) using online and offline media. 2) Sales Promotion & Event, which is an integrated sales promotion marketing communication activity carried out by PT.Telkom Indonesia (Regional III). 3) Personal Selling, sales made by salesforce that are done offline. 4) Direct Marketing, marketing that is done by contacting potential consumers directly. 5) Top of Mind, which is PT.Telkom Indonesia's (Regional III) way to maintain that IndiHome is always at the top of people's minds. Researchers found top new findings from interviews with informants either key first or supporters. According to him, at the research stage, it must make adjustments to management provisions in order to carry out events in a company in a structured and organized manner so that IndiHome can become a Top of Mind brand.Keywords-Marketing Communication, PT. Telkom Indonesia (Regional III), Top of Mind